The influence of neutral MDP-Na salt on dentin bond performance and remineralization potential of etch-&-rinse adhesive - Mingxing Li; Haiyan Zheng; Yuedan Xu; Yuan Qiu; Yinlin Wang; Xiaoting Jin; Zhengyi Zhang; Ling Zhang; Baiping Fu (BMC, 2024)
Abstract Objectives To investigate the effect of neutral 10-methacryloyloxydecyl dihydrogen phosphate salt (MDP-Na) on the dentin bond strength and remineralization potential of etch-&-rinse adhesive. Methods Two experimental etch-&-rinse adhesives were formulated by incorporating 0 wt% (E0) or 20 wt% (E20) neutral MDP-Na into a basic primer. A commercial adhesive, Adper Single Bond 2 (SB, 3 M ESPE), served as the control. Sixty prepared teeth were randomly allocated into three groups (n = 20) and bonded using either one of the experimental adhesives or SB. Following 24 h of water storage, the bonded specimens were sectioned into resin-dentin sticks, with four resin-dentin sticks obtained from each tooth for microtensile bond strength (MTBS) test. Half of the sticks from each group were immediately subjected to tensile loading using a microtensile tester at a crosshead speed of 1 mm/min, while the other half underwent tensile loading after 6-month incubation in artificial saliva (AS). The degree of conversion (DC) of both the control and experimental adhesives (n = 6 in each group) and the adsorption properties of MDP-Na on the dentin organic matrix (n = 5 in each group) were determined using Fourier-transform infrared spectrometry. Furthermore, the effectiveness of neutral MDP-Na in promoting the mineralization of two-dimensional collagen fibrils and the adhesive-dentin interface was explored using transmission electron microscopy and selected-area electron diffraction. Two- and one-way ANOVA was employed to assess the impact of adhesive type and water storage on dentin bond strength and the DC (α = 0.05). Results The addition of MDP-Na into the primer increased both the short- and long-term MTBS of the experimental adhesives (p = 0.00). No difference was noted in the DC between the control, E0 and E20 groups (p = 0.366). The MDP-Na remained absorbed on the demineralized dentin even after thorough rinsing. The intra- and extra-fibrillar mineralization of the two-dimensional collagen fibril and dentin bond hybrid layer was confirmed by transmission electron microscopy and selected-area electron diffraction when the primer was added with MDP-Na. Conclusions The use of neutral MDP-Na results in high-quality hybrid layer that increase the dentin bond strength of etch-&-rinse adhesive and provides the adhesive with remineralizing capability. This approach may represent a suitable bonding strategy for improving the dentin bond strength and durability of etch-&-rinse adhesive.